(untitled) (Bheshaja: Journal of Central Ayurveda Campus, 2025)
Lifestyle disorders such as obesity, type 2 diabetes, hypertension, and metabolic syndrome are on the rise globally due to poor diet, sedentary habits, and stress. Both intermittent fasting (IF) and Ayurvedic principles emphasize natural rhythms, digestion, and detoxification of the body, offering promising non-pharmacological approaches to address these disorders. The goal of this article is to review and analyze the synergistic effect of intermittent fasting and Ayurvedic principles in the prevention and management of lifestyle disorders. A narrative review was conducted using classical Ayurvedic texts and modern scientific literature from Research journals, Portals, Blogs. Studies discussing the physiological effects of IF and Ayurvedic regimens such as Dinacharya, Ritucharya and Upavasa were included to explore conceptual and practical overlaps. The combined approach of IF and Ayurveda shows enhanced benefits in metabolic regulation, hormonal balance, inflammation reduction, digestive function (Agni), reduction of metabolic toxins (Ama) and circadian alignment. Both systems support improved insulin sensitivity, weight control, and gut health, with Ayurveda offering personalized dietary and lifestyle guidance that complements IF. Further clinical research is needed to validate these integrative protocols and promote their practical application in modern healthcare.